THE PROSPECT OF INTEGRATION THROUGH INCOMPLETE CONTRACT - Ausiandra, Yusuf (Indonesian Journal of International Law, 2013)
Law and economics (L&E) as an interdisciplinary tool bridges the realms of analytical economics and law. Albeit widely accepted as theoretically separate, the construction of international public law treaties could be paralleled at a structural formative level with private contracts. Incomplete contracting as a branch of contractual L&E permits to comprehend the dynamics of drafting an economically efficient contract and hence also international treaties. Incomplete contracting analysis hereby would be applied to the development of the Association of Southeast Asian Nations (ASEAN) regarding cooperation and the possibility of future integration from a contractual standpoint.